Efeitos da presença do coelho na avaliação e tolerância de som desagradável - Rabello, Jaqueline Picanço (Universidade Federal de São Carlos, 2017)
The coexistence between man and the animals that surround him has been occurring for the last ten thousand years. Benefits of living with pets have been reported by different areas of knowledge and are related to physical and mental health, being associated with protection factors against depression, anxiety, among others. However, the deficient operationalization of procedures in this area makes it difficult to understand the phenomenon and the scientific production. The present study had as objective to verify the influence of the presence of a rabbit in the tolerance to unpleasant sonorous stimulus. Thirty adults, aged 20 to 34 years (M = 24.3 and SD = 3.2) participated in the study. Participants were exposed to unpleasant sounds by means of headphones coupled to a portable computer in three different conditions. In the Rabbit condition, participants listened to the sound as they watched a rabbit in front of its cage. In the Movie condition, participants listened to the sound while watching a video of the same rabbit inside their cage. In turn, in the Control condition, the participants listened to the sound without distracting stimulus. The time of permanence in the conditions, heart rate and galvanic conductance of the skin were measured, as well as the responses provided to a Scale of Differential Semantics and Visual Analog Humor Scale. The results indicated that participants assessed more positively and remained longer, in seconds, under Film (M = 253.27, SD = 177.99) and Rabbit (M = 255.37s, SD = ± 179.34 ), when compared to Control (M = 172.4, SD = ± 169.9). The data showed that visual contact with the rabbit, physically and also through the video, increased the tolerance to the unpleasant sound stimulus, and also promoted a better evaluation of the participants regarding the stressful situation.
Keywords: Animais de estimação; Coelhos; Estimulação aversiva; Condutibilidade da pele; Frequência cardíaca; Diferencial semântico; Pets; Rabbits; Aversive stimuli; Semantic differential technique; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::ESTADOS SUBJETIVOS E EMOCAO